Bridge?embankment interaction under transverse ground excitation. - Kotsoglou, Anastasios (Earthquake engineering & structural dynamics.)
Seismic performance and dynamic response of bridge?embankments during strong or moderate ground excitations are investigated through finite element (FE) modelling and detailed dynamic analysis. Previous research studies have established that bridge?embankments exhibit increasingly flexible performance under high-shear deformation levels and that soil displacements at bridge abutment supports may be significant particularly in the transverse direction. The 2D equation of motion is solved for the embankment, in order to evaluate the dynamic characteristics and to describe explicitly the seismic performance and dynamic response under transverse excitations accounting for soil nonlinearities, soil?structure interaction and imposed boundary conditions (BCs). Using the proposed model, equivalent elastic analysis was performed so as to evaluate the dynamic response of approach embankments while accounting for soil?structure interaction. The analytical procedures were applied in the case of a well-documented bridge with monolithic supports (Painter Street Overcrossing, PSO) which had been instrumented and embankment participation was identified from its response records after the 1971 San Fernando earthquake. The dynamic characteristics and dynamic response of the PSO embankments were evaluated for alternative BCs accounting for soil?structure interaction. Explicit expressions for the evaluation of the critical embankment length Lc are provided in order to quantify soil contribution to the overall bridge system under strong intensity ground excitations. The dynamic response of the entire bridge system (deck?abutments?embankments) was also evaluated through simplified models that considered soil?structure interaction. Results obtained from this analysis are correlated with those of detailed 3D FE models and field data with good agreement.